CC genotype donors for the interleukin‐28B single nucleotide polymorphism are associated with better outcomes in hepatitis C after liver transplant. (29th October 2012) - Firpi, Roberto J.; Dong, Huijia; Clark, Virginia C.; Soldevila‐Pico, Consuelo; Morelli, Giuseppe; Cabrera, Roniel; Norkina, Oxana; Shuster, Jonathan J.; Nelson, David R.; Liu, Chen
Abstract: Background/Aims: Interleukin‐28B (IL‐28B) polymorphism is the strongest pretreatment predictor of viral clearance in the hepatitis C (HCV) population. Donor and recipient IL‐28B genomic background may play an important role in post‐transplant HCV recurrence. We sought to examine the role of IL‐28B polymorphisms of donor and recipients in liver transplant patients with recurrent HCV and its impact on the response to interferon‐based therapy. Methods: The cohort study consisted of 135 adult liver transplant patients who received interferon‐based therapy for recurrent HCV between 1996 and 2005 at the University of Florida. IL‐28B single nucleotide polymorphism ( rs . 12979860) was characterized using liver tissue from all donors and recipients. Results: The CC genotype was observed in approximately 30% of donors and recipients. Sustained viral response (SVR) to HCV therapy was 100% if both recipient and donor were CC genotype, while the SVR was only 25% if neither donor nor recipient had a CC genotype. (Recipient, P  = 0.025, Donor, P  < 0.001). Recipients and donors with CC genotype had less fibrosis than recipients with genotypes CT and TT, but the difference was not statistically significant. IL‐28B genotype did not seem to play a role in the overall survival in these patients. Conclusion: In conclusion, recipient and donor CC genotype is associated with a better treatment response to interferon‐based therapy after liver transplant. Our study suggests that using CC genotype donor livers for HCV patients may improve the overall clinical outcome after liver transplantation.